Manajemen Pelayanan Jamaah Umrah Dalam Menyesuaikan Kenaikan Biaya Umrah Di PT Zafa Mulia Mandiri Palembang - Rista Muamala; Hasril Atieq Pohan (CV. ITTC INDONESIA, 2026)
The increase in Umrah costs that has occurred in recent years has become a challenge for Umrah travel agencies, especially in maintaining the quality of service to pilgrims. PT Zafa Mulia Mandiri Palembang, as one of the Umrah pilgrimage travel organizers, is required to be able to adjust its service management to continue to provide satisfaction to pilgrims amidst increasing operational costs. This study aims to determine and analyze the management of Umrah pilgrim services in adjusting to the increase in Umrah costs at PT Zafa Mulia Mandiri Palembang. The research method used is a qualitative method with a descriptive approach. Data collection techniques were carried out through interviews, observation, and documentation. The results show that PT Zafa Mulia Mandiri Palembang adjusted its service management by increasing operational efficiency, transparency of costs to pilgrims, optimization of administrative services, guidance of manasik (ritual practice), and improving the quality of human resources. These adjustments were made without reducing the essence of Umrah pilgrimage services, so that pilgrims' trust and satisfaction were maintained despite the increase in Umrah costs